A Legal Analysis of Medical Malpractice in the Indonesian Legal System - Astri Revinesia (Outline Publisher, 2025)
This study examines the legal phenomenon of medical malpractice in the Indonesian legal system. The background is based on the need for legal certainty, patient protection, and certainty of responsibility of medical personnel and health care facilities in the event of alleged negligence. The study aims to (1) map the regulation of medical malpractice in Indonesian laws and regulations and (2) analyze the legal provisions that can be applied when malpractice occurs. The method used is normative legal research with a statutory approach , a conceptual approach, and case studies. Primary legal materials include the Law on Medical Practice, the Hospital Law, the Health Law , and implementing regulations related to informed consent and the obligation to make medical records; secondary legal materials are obtained from literature and relevant research results. The results of the study indicate that legal responsibility for alleged medical malpractice is spread across three regimes: (a) civil—through therapeutic relationships and unlawful acts, including hospital responsibility for negligence of health workers; (b) criminal—based on the element of negligence (culpa) that results in consequences for the patient in accordance with statutory provisions ; and (c) administrative/disciplinary — including compliance with professional standards and standard operating procedures, the obligation to have a STR/SIP, the creation of medical records, and the application of professional disciplinary mechanisms. The role of informed consent and the completeness of medical records occupy a central position in proving